The Effect of Argument Driven Inquiry (ADI) Model on the Scientific Argumentation Ability of High School Students on the Topic of Light Waves - Fuadah, Maghfirotul Ismi; Mubarok, Husni; Suliyanah, Suliyanah (Mitra Edukasi dan Publikasi, 2023)
Scientific argumentation is the process of strengthening claims through critical analysis based on supporting evidence and logical reasons, where the evidence can include facts that can be accepted as truth. This study aims to describe the improvement of students' scientific argumentation abilities on the topic of light waves after applying the ADI learning model. This research uses the type of True Experimental with a Control Group Pretest and Posttest design. The data collection technique in this study was the test method. The results of this study indicate an increase in scientific argumentation abilities on the topic of light waves after applying the ADI learning model. The results of the scientific argumentation ability of experimental class students were higher than the control class, the experimental class got an n-gain of 0.60 with a medium category, while the control class got an n-gain of 0.26 with a low category. In the pretest, experimental, and control classes, students were at levels 1, 2, and 3. The posttest results of experimental class students who experienced increased scientific argumentation at levels 4 and 5. Meanwhile, the posttest results of students in the control class were relatively the same as the pretest results, namely at levels 1, 2, and 3. In addition, the Cohen's Effect Size analysis results showed a value of 0.88 in the strong criteria. It can be concluded the ADI learning model affects learning to improve students' scientific argumentation abilities of senior high school students on the topic of light waves.